(untitled) (Research, Society and Development, 2021)
Introduction: In a surgical woundone of the techniques used to help the healing process is the suture. After dental extractions, the resulting surgical site is, in most cases, healed via secondary healing, making the oral surgeon’s best interest to keep the blood clot fixed in the wound and foreign bodies out of it. Objectives: This study has the objective of demonstrating the Paz’s suture technique. Methodology: The Paz’s suture technique is a modification of the figure of eight technique proposed by Hupp, for better results; use the unabsorvable monofilamented nylon sutures. To start, choose a point in either side, in this case, mesial of the vestibular side. The first puncture is made in this elected point and the second one follows in distal part of the lingual side. The third puncture is made in the mesial part of the lingual side where the suture is pulled and a 5mm strap is formed. The final puncture is made in the distal part of the vestibular side where and the needle is past underneath the strap and pulled to form the knot. As a result, two X figures are formed vertically to one another. Results and conclusion: Paz’s suture propose better security of the blood clot and an extra barrier against foreign bodies and with this article, we seek to promote researches about Paz’s suture to better understand it.